The Saccharomyces cerevisiae COQ10 gene encodes a START domain protein required for function of coenzyme Q in respiration - Barros, M. H.; Johnson, A.; Gin, P.; Marbois, B. N.; Clarke, C. F.; Tzagoloff, A. (Amer Soc Biochemistry Molecular Biology Inc, 2005)
Deletion of the Saccharomyces cerevisiae gene YOL008W, here referred to as COQ10, elicits a respiratory defect as a result of the inability of the mutant to oxidize NADH and succinate. Both activities are restored by exogenous coenzyme Q(2). Respiration is also partially rescued by COQ2, COQ7, or COQ8/ABC1, when these genes are present in high copy. Unlike other coq mutants, all of which lack Q(6), the coq10 mutant has near normal amounts of Q(6) in mitochondria. Coq10p is widely distributed in bacteria and eukaryotes and is homologous to proteins of the aromatic-rich protein family Pfam03654 and to members of the START domain superfamily that have a hydrophobic tunnel implicated in binding lipophilic molecules such as cholesterol and polyketides. Analysis of coenzyme Q in polyhistidine-tagged Coq10p purified from mitochondria indicates the presence 0.032-0.034 mol of Q(6)/mol of protein. We propose that Coq10p is a Q(6)-binding protein and that in the coq10 mutant Q(6) it is not able to act as an electron carrier, possibly because of improper localization.